Resonanzen und Dissonanzen: Hartmut Rosas kritische Theorie in der Diskussion - Peters, Christian Helge; Schulz, Peter (transcript, 2017)
In his new work, Hartmut Rosa has developed the concept of resonance as a counter-term and potential solution for the social problem of acceleration. In this way, resonance is equally the analytical and normative basis of his critical theory. The contributions in this volume seek to open interdisciplinary discussions around this concept, considering it from a range of different perspectives. The anthology provides both an introduction to, and discussion of, the concept of resonance, as well as an in-depth critical analysis of other key concepts in contemporary social science discourse.